THE EFFECTS OF STUDENT’S PERCEPTION ON LEARNING TECHNIQUES AND CRITICAL THINKING TOWARD STUDENT’S READING SKILL AT GOVERNMENT SENIOR HIGH SCHOOLS IN DEPOK - Nujuluddin Siregar (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
The purpose of this research is to know The effect of Learning Technique towards students’ reading skills and The effect of Critical Thinking towards students’ reading skills and also the effect both of them at Government Senior High School 1 in Depok. This research has been done in 6 Months (October 2012– March 2013). The sample is 30 students with simple random sampling taken from population. The method used into three variables. Students’ Learning Technique (X1), Students’ Critical Thinking (X2) and Reading Skills (Y). The techniques of data analysis used are descriptive statistics, validity and reliability, normality and also hypothesis test and correlation from statistic calculation and SPSS computer program. According to the data X1 vs Y, the writer concluded that any significant relationship between students’ reading skills and their learning technique in degree of 67,24 %, and also the data of X2 vs Y relationship between students’ reading skills and their learning technique in degree of 59,29 %.Keywords: Learning technique, critical thinking and reading skill.